Palliative Care Teams in the German Comprehensive Cancer Centers - Gahr, Susanne; Berendt, Julia; Lödel, Sarah; Ostgathe, Christoph; Simon, Steffen T.; Tewes, Mitra; Zader, Kirsten; Schwartz, Jacqueline; Neukirchen, Martin (Deutsche Medizinische Wochenschrift, 2019)
BACKGROUND: A palliative care team is recognized as a quality indicator in the consultation and care of patients with a tumor disease and is used nationally (92 %) in the National Cancer Institutes, model of the German Comprehensive Cancer Center (CCC). This begs the question of how palliative care teams are presently integrated into the CCCs. METHOD: From July to August 2017, a paper-based quantitative survey of 16 locations of the CCCs, supported to that date, gathered information on the existence, personnel situation, use and prospects of a specialized inpatient palliative care service. The survey was addressed to the heads of the palliative medical units of the CCCs. The data were evaluated in SPSS (frequency, median, mean, range). RESULTS: Fifteen CCCs took part in the survey (response 94 %). Thirteen of the fifteen CCCs have a service that also treats palliative patients. Twelve of thirteen CCCs of these are attainable during regular working hours (8a. m.-4 p. m. on weekdays). All services are staffed by physicians, additional eleven are staffed by nurses. Seven services are besides physicians and nurses joined by other professions. In 2016, 4482 median co-treatments were provided by the services, 80 % of these as additional charges without revenue and without codable OPS. In 2017, five centers plan to charge ZE 2017-133, two centers ZE 60 and three centers both intend to charge ZE 2017-133. CONCLUSIONS: Services for palliative patients exist generally in the German CCCs, but only half of them satisfy the condition of multi-professionality required for the fulfillment of the german guidelines. The new surcharge introduced in 2017, which can be charged on an hourly basis, could create improvements in this regard and contribute to cost recovery. Thus, contrary to the previous arrangement, essential and reasonable performances with a time of treatment of less than seven days can be charged.
EVALuna2:204833